(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Today, relations between the European Union and Central Asia are radically changing and gaining new significance. The reason for this is the opening policy of the region. This strategy is more successful than previous one. The new strategy focuses on economy, policy and culture, which wasn’t paid enough attention in the old strategy. Furthermore, Aspects not previously mentioned in the old strategy adopted by the EU such as border security, cooperation in the customs service, investment in Central Asian youth through scholarships, supporting innovative technology and knowledge.